Peran Sanad dalam Keshahihan Hadits (Studi Takhrij Hadis-hadis Masyhur di Masyarakat) - Nurhidayati Ismail (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Sanad is important in Islam. The existence of sanad in a hadith determines whether a hadith can be accepted (Maqbul) or ditolah (mardud). In addition, many of the famous (popular) hadiths circulating in the community are not necessarily the hadith considered shahih or even false. This study aims to examine several hadiths that are popular in the community. The method used in this study is the takhrij method, by examining the historical sanad-sanad in question. In this study, the history studied was three pieces. From the results of oenelitian, the three histories that were originally considered hadith, it turns out that none of the hadiths have a history from the Prophet Muhammad SAW, some are maudhu' (false), and are also popular Arabic syi'ir.